Anestesia peridural com ropivacaína com ou sem clonidina nas hemorroidectomias e dor pós-operatória - Joao Florencio de Abreu Baptista (2014)
The pain in postoperative hemorrhoidectomy surgery is a complication with unpleasant consequences for the patient. Anesthetic techniques that provide better relief and safety continue to be develop. Objectives: To examine the effect of clonidine, 4 ìg/kg, added to ropivacaine, in epidural anestesia in hemorrhoidectomy, in: 1- postoperative analgesia; 2- alterations in blood pressure and heart rate; 3- correlation between the dose used and the age of patients; 4- correlation between the pain score and body mass index. Methods: We studied patients of both genders, aged from 20 to 70 years, physical status I or II (ASA), undergoing hemorrhoidectomy were randomly divided into two groups: Control (n = 38) who received epidural anesthesia with 14 mL of 0.75% ropivacaine plus 0,0266 mL of 0.9% saline; Experiment (n = 42) who received epidural anesthesia with 14 mL of 0.75% ropivacaine plus 4 ìg/kg of clonidine. In perioperative and postoperative parameters were evaluated: systolic blood pressure (SBP) and diastolic (DBP), heart rate (HR), pulse oximetry (SpO2) and ECG. The intensity of postoperative pain was assessed with the aid of a visual analogue scale (VAS) at 4 h, 8 h and 12 h after onset of anesthesia. We calculated the analgesic consumption in the first 12 hours and the number of requests for analgesia. The degree of patient satisfaction and postoperative complications were recorded. Results: The two groups were similar in gender distribution of patients and the values of age, height, weight, body mass index (BMI) and duration of surgery. There was a difference between the time 4 h, with an increase in VAS score, with 8 h and 12 h times. The Experimental group showed a correlation of EVA 12 h with age (p <0.05) in that as age increases decreases the score of EVA 12 h. The SBP, DBP and HR differed between the initial time and the other times, with lower values, no statistical difference and after 15 minutes, at times 15, 30 and 45 minutes. We found differences between the two groups in the initial moment where there is a decrease in HR from baseline to the other moments. There was no difference between times 15, 30 and 45 min. We also found a statistically significant difference, the heart rate values, at times 15, 30 and 45 min. between groups Control and Experiment. Conclusion: Epidural anesthesia with ropivacaine 0,75% associated with clonidine, 4 ìg/kg of weight, in hemorrhoidectomies, showed a better analgesic efficacy at 4 h in the clonidine group with less use of analgesics in the postoperative period. Arterial blood pressure and heart rate were maintained in both groups. A minor value of VAS was observed with the increase of age without any significant difference between VAS and body mass index.